Multi-direction health monitoring with carbon nanotube film strain sensor - Tao Xu; Qingdong Qiu; Shaowei Lu; Keming Ma; Xiaoqiang Wang (International Journal of Distributed Sensor Networks)
Carbon nanotubes have been the focus study in composite health monitoring fields due to its better performances and excellent mechanical property. Yet, the performance for multi-direction strain monitoring of the carbon nanotube film sensor has not been concerned. Therefore, this article focuses on the strain monitoring with the circular carbon nanotube film sensor which exhibits the characteristics for multi-direction strain measurement. The carbon nanotube film is fabricated through agitation, sonication, centrifugation, and vacuum filtration. Using the molding machine, the circular carbon nanotube film senor and the rectangular carbon nanotube film sensor are surface bonded with composite laminates, respectively, to compare the multi-direction strain monitoring characteristics. With the prepared laminates, the stretching tests are committed at 0°, 30°, 60°, and 90° using the universal tensile machine. Experimental results of the circular sensor show the steady sensing coefficients that fluctuate between 59.51676 and 60.9273 at different degrees. By comparison, the rectangular sensor presents different sensing coefficients from vertical stretching test and horizontal stretching test. Therefore, the circular carbon nanotube film exhibits multi-direction strain monitoring that can serve as an efficient tool for structural health monitoring of composite structures.